(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
The current research investigates Mapping Issues of Textile Industry of Pakistan with Trade Policy Framework. Data were collected from Primary as well as secondary sources It is a statistical research technique in decision making that is used for the selection of a limited number of tasks that produce significant overall effect. It separates the few major problems from the many possible problems. It is named after Vilfredo Pareto, a 19th-century Italian economist. It can summarize all types of data. It can be applied to almost anything. It was revealed that four issues may be solved by the Government through trade policy of Pakistan as shown in figure 7-12 below. First and issue that in the international Markets Preferential Treatment is provided to the competitors and the second issue about Imposition of Anti-dumping duties on Pakistans exports may be solved by Rationalizing Tariff Protection Policy (TPP) High tariff protection maintained over a period of time tends to erode competitiveness and affects consumer welfare. Therefore to protect Industry from High Tariffs, Ministry of Commerce will adopt some guiding principles to create a competitive environment that caters for dual aspects of providing level playing field for Pakistani firms in international markets; By Signing Favorable international agreements, Promote competitive markets in Pakistan, Ensure conformity to international agreements and practices, Promote domestic and foreign investment, Create level playing field for Pakistani firms in international as well as domestic markets, Due consideration to consumer welfare, Cater to the changing needs of Pakistans economy and create an enabling environment to pursue the legitimate goal of Industrialization in Pakistan. Due to the prompt implementation of the above policy measure by Government on 12th December 2013 European Union granted GSP-Plus status to Pakistan, It gives exporters duty-free access to 27 European countries. GSP (Generalized system of Preference) is exemption of WTO member countries from tariffs by considering as a least developed nation and granted till 2017. It is a chance to export more than US1 billion worth of products and earn profits of more than Rs1 trillion per year.